Regional Autonomy from the Perspective of Islamic Constitutional Law: Conceptual Analysis and Normative Basis - Salpiyah Salpiyah; Nur Anggieta Putri; Kurniati Kurniati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research examines regional autonomy from the perspective of Islamic constitutional law. The study is prompted by the importance of regional management through the delegation of authority from the central government to local regions to achieve social welfare. The objective of this research is to explore the normative foundations of autonomy in Islam, formulate its implementation mechanisms based on Sharia principles, and analyze its impact on development and welfare. The research employs a qualitative method based on library research with a descriptive-analytical approach. The results indicate that regional autonomy has a strong theological basis in the Qur'an, Hadith, and the historical practice of Islamic governance through the delegation of authority to governors (amir). The implementation mechanism prioritizes the principles of amanah (trustworthiness), shura (consultation), and hisbah (supervision) to ensure policy justice. Furthermore, regional autonomy has a positive impact on increasing democratic participation and the responsiveness of public services, though it requires strengthened supervision to prevent disparities and the abuse of power.